Role of Nutrition in Periodontal Health - A Review - Mahajan, Ajay; Mahajan, Poonam; Thakur, Saroj; Kashyap, Divya; Kumar, Amit (The Journal of Dentists, 2014)
The relation between the systemic and oral health is now well established. Researches have shown that many systemic diseases either cause or exaggerate the course of the certain periodontal conditions. Nutrition plays an important role in growth, development as well as the maintenance of the hard and soft tissue and also has a significant influence on the host immune response. Nutritional deficiencies therefore adversely affect periodontal health, causing as well as affecting the course and severity of periodontal diseases. The purpose of this article is thus to elaborate in detail the interrelation between the nutrition, periodontal health and diseases.